Podcasts and Papers: Using AI to Engage Undergraduates in Scientific Literacy in Biology - Shem Unger; Mark Rollins (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: Artificial Intelligence (AI) is emerging as a valuable tool for science education, for both students and instructors. This study was conducted to investigate the efficacy of using AI-generated podcasts to introduce undergraduates to primary scientific literature as a teaching pedagogy. Methodology: Google NotebookLM was used to generate audio podcasts on ten different scientific journal articles for an undergraduate ecology course. Students were surveyed on how engaging, informative, and helpful podcasts were, and whether they helped introduce them to the research article. Data were collected from Likert-scale questionnaires and short responses and analyzed both quantitatively and qualitatively. Main Findings: The majority of students found AI-generated audio podcasts an engaging and effective learning method for increasing science literacy and understanding. No change was noted across the class in student perceptions of podcasts, indicating that the majority of students found AI podcasts helped them learn about scientific research, with 35% not realizing the podcast was AI. These findings reveal the potential to increase science literacy through our methodology if incorporated across various fields of science education. Novelty/Originality of this study: This study provides evidence that AI-generated podcasts can be used as a new method to introduce biology students to peer-reviewed scientific articles. Other educators can use similar free audio podcasts across subjects to engage undergraduate students in science. The findings add to our body of knowledge on AI and on how educators can utilize podcasts as a powerful pedagogical tool for teaching science.